Analogous Atomic and Electronic Properties between VN and VNCB Defects in Hexagonal Boron Nitride - Chang-Youn Moon; Kee-Suk Hong; Yong-Sung Kim (Advances in Condensed Matter Physics)
We investigate defect properties in hexagonal boron nitride (hBN) which is attracting much attention as a single photon emitter. Using first-principles calculations, we find that nitrogen-vacancy defect VN has a lower energy structure in C1h symmetry in 1− charge state than the previously known D3h symmetry structure. Noting that carbon has one more valence electron than boron species, our finding naturally points to the correspondence between VN and VNCB defects with one charge state difference between them, which is indeed confirmed by the similarity of atomic symmetries, density of states, and excitation energies. Since VNCB is considered as a promising candidate for the source of single photon emission, our study suggests VN as another important candidate worth attention, with its simpler form without the incorporation of foreign elements into the host material.